An investigation on lecturers’ perceptions of communicative language teaching in an Afghan Public University / Abdullah Noori - Noori, Abdullah (2017)
Communicative Language Teaching (CLT) is based on the theory of language as communication. It is one of the most widely utilised language teaching approaches. Many studies have been conducted to investigate the perceptions of teachers toward CLT in both ESL and EFL contexts, but some, particularly those conducted in EFL context, have reported that the application of CLT was challenging. However, as far as the Afghan EFL context is concerned, there is a lack of empirical research investigating the issue. Hence, the purpose of this study is to investigate the perceptions of Afghan EFL lecturers toward CLT, and the potential challenges they face in CLT implementation. The study also aims to examine if there is any significant relationship among teachers use of CLT classroom activities, the challenges in a CLT classroom, and teachers’ demographic profiles. This study utilises a quantitative research approach in which a survey questionnaire was given to a total of 32 EFL lecturers teaching at the English Department of a public university. The respondents took part in the study voluntarily. The data gathered through the questionnaire was analysed using SPSS v.23 in which both descriptive and inferential statistics such as mean scores, standard deviation, t-tests, One-Way ANOVA, and Person-correlation were used to test hypotheses. The results of the study revealed that Afghan EFL lecturers had a clear understanding of communicative techniques and the underlying principles of CLT. The study also found that the lecturers maintained positive perceptions toward using CLT activities, as there was evidence of a number of major CLT activities conducted in their classrooms. In the meantime, the lecturers also revealed that they face certain challenges (students related, teacher related, system related, and CLT related) in implementing CLT effectively in their classes. The study results also reveal a significant correlation between student and system related challenges and teachers’ perceptions of using CLT activities; however, no significant correlations were found among teachers’ demographic profiles, CLT perceived challenges, and use of CLT classroom activities. Finally, the study provides some implications to the MoHE considering which might be valuable for effective implementation of CLT in Afghan EFL context.